The Effect of Thermocycling on Fracture Resistance of CAD- CAM and 3D Printing Provisional Prosthesis - Hadi, Maab Qassim; Dulami , Suha Fadhil (Journal of Techniques, 2022)
This study aims to assess how thermal cycling affected the fracture strength of temporary restorations made using additive 3D printing procedures and computer-aided design- computer-assisted manufacturing (CAD/CAM), subtractive (milling) methods. For full coverage crowns, a dento form upper molar tooth was created. A second oral scanner digitally scanned developed model. Duplication of the metal dies was made using the master die (chrome cobalt alloy). A total of 40 samples were created and split into two groups: 20 were created using CAD/CAM technology with a (Bilkim) CAD PMMA disc and 20 were created using 3D printing with Asiga dentatooth resin. Thermal cycles (1250 cycles, 5-55 °C) were applied to 10 samples from each group. After that, a universal testing device determined the fracture resistance for each sample. The mean with standard deviation values of fracture resistance were recorded for the milled group before thermocycling (560.50 ±83.581 newton) and after thermocycling (901.00± 311.598 newton) meanwhile the mean ± stander deviation value was recorded with the printed group before thermocycling (1972.50±399.181 Newton) and after thermocycling (2284.10±239.001 Newton), it was found that the printed group recorded statistically significant higher fracture resistance mean value than the milled group. Provisional crowns constructed using the 3D printing technique showed higher fracture resistance compared to the temporary milled crowns.